Index: The Book of Statistical ProofsStatistical Models ▷ Count data ▷ Multinomial observations ▷ Maximum log-likelihood

Theorem: Let $y = [y_1, \ldots, y_k]$ be the number of observations in $k$ categories resulting from $n$ independent trials with unknown category probabilities $p = [p_1, \ldots, p_k]$, such that $y$ follows a multinomial distribution:

$\label{eq:Mult} y \sim \mathrm{Mult}(n,p) \; .$

Then, the maximum log-likelihood for this model is

$\label{eq:Mult-MLL} \mathrm{MLL} = \log \Gamma(n+1) - \sum_{j=1}^{k} \log \Gamma(y_j+1) - n \log (n) + \sum_{j=1}^{k} y_j \log (y_j) \; .$

Proof: With the probability mass function of the multinomial distribution, equation \eqref{eq:Mult} implies the following likelihood function:

$\label{eq:Mult-LF} \begin{split} \mathrm{p}(y|p) &= \mathrm{Mult}(y; n, p) \\ &= {n \choose {y_1, \ldots, y_k}} \prod_{j=1}^{k} {p_j}^{y_j} \; . \end{split}$

Thus, the log-likelihood function is given by

$\label{eq:Mult-LL} \begin{split} \mathrm{LL}(p) &= \log \mathrm{p}(y|p) \\ &= \log {n \choose {y_1, \ldots, y_k}} + \sum_{j=1}^{k} y_j \log (p_j) \; . \end{split}$ $\label{eq:Mult-MLE} \hat{p} = \left[ \hat{p}_1, \ldots, \hat{p}_k \right] \quad \text{with} \quad \hat{p}_j = \frac{y_j}{n} \quad \text{for all} \quad j = 1, \ldots, k \; .$

Plugging \eqref{eq:Mult-MLE} into \eqref{eq:Mult-LL}, we obtain the maximum log-likelihood of the multinomial observation model in \eqref{eq:Mult} as

$\label{eq:Mult-MLL-s1} \begin{split} \mathrm{MLL} &= \mathrm{LL}(\hat{p}) \\ &= \log {n \choose {y_1, \ldots, y_k}} + \sum_{j=1}^{k} y_j \log \left( \frac{y_j}{n} \right) \\ &= \log {n \choose {y_1, \ldots, y_k}} + \sum_{j=1}^{k} \left[ y_j \log (y_j) - y_j \log (n) \right] \\ &= \log {n \choose {y_1, \ldots, y_k}} + \sum_{j=1}^{k} y_j \log (y_j) - \sum_{j=1}^{k} y_j \log (n) \\ &= \log {n \choose {y_1, \ldots, y_k}} + \sum_{j=1}^{k} y_j \log (y_j) - n \log (n) \; . \end{split}$

With the definition of the multinomial coefficient

$\label{eq:mult-coeff} {n \choose {k_1, \ldots, k_m}} = \frac{n!}{k_1! \cdot \ldots \cdot k_m!}$

and the definition of the gamma function

$\label{eq:gam-fct} \Gamma(n) = (n-1)! \; ,$

the MLL finally becomes

$\label{eq:Mult-MLL-s2} \mathrm{MLL} = \log \Gamma(n+1) - \sum_{j=1}^{k} \log \Gamma(y_j+1) - n \log (n) + \sum_{j=1}^{k} y_j \log (y_j) \; .$
Sources:

Metadata: ID: P386 | shortcut: mult-mll | author: JoramSoch | date: 2022-12-02, 17:22.